Influence of nanoclay on the fire resistance properties of epoxy-based intumescent retardant coatings for steel plate - Do Dang, Trung (VNU Journal of Science: Natural Sciences and Technology, 2023)
The intumescent retardant coating was fabricated by a combination of epoxy binder and flame-retardant ingredients for the steel plate. This paper investigates the influence of nanoclay content on improving fire properties of intumescent fire-retardant coatings. The fire performances of the coatings were determined by a fire test at 950 o C for one hour. The coating degradation was characterized by Thermal gravimetric analysis (TGA). The morphology, composition of char was studied by Fourier transform infrared spectra (FTIR), scanning electron microscopy (SEM), and energy dispersive X-ray spectra (EDS). The results revealed that the intumescent coating containing 3 wt.% of nanoclay showed the best reduction in substrate temperature compared to the intumescent coating without nanoclay. The results also concluded that nanoclay increased fire protective performances of the intumescent coating.